Down to the Last Dollar: Utilizing a Virtual Budgeting Exercise to Recognize Implicit Bias - Christin Traba; Aditi Jain; Kimberly Pianucci; Jennifer Rosen-Valverde; Sophia Chen (Association of American Medical Colleges, 2021)
Introduction As social determinants of health and implicit bias are recognized as critical components of medical education, there is a need for novel approaches beyond didactics. We developed a small-group budgeting exercise to simulate the impact of poverty. Pediatrics exemplifies the effects of poverty on the family. This exercise allowed students to recognize the effects of food insecurities on health and reflect on biases regarding patients living in poverty. Methods The virtual interactive budgeting exercise (1.5-2 hours) introduced third-year pediatric clerkship students to the challenges faced by a single parent living in poverty, requiring them to make choices on which budget items were most important. Students attempted to balance budgets within small breakout groups, followed by a group reflection on biases encountered. A faculty facilitator then debriefed with the larger group. Results Within the first four rotations of the 2020-2021 academic year, 75 students completed the budgeting exercise and reflection, with 61 students completing the postexercise survey evaluation. Between 94% and 98% rated the objectives as met to a moderate, considerable, or very high degree. In addition, 98% of students noted the group discussion heightened their awareness regarding biases, and 95% agreed or strongly agreed the activity was conducted virtually without difficulty. Discussion This simulated budgeting exercise provides a well-rounded experience for medical students, that can be administered at either the preclerkship or clerkship level, at a minimal cost, with interactive engagement of students in a virtual environment and reflection on biases within a group context.